Humanity, Socio-political Community and Universality/Difference: Andrew Linklater, Critical Theory and Global Politics - Agcan, Muhammed A. (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2013)
Recent debates in international relations theory are largely about the possibility of moral, social and political conceptualization of the international as a distinct sphere of human existence. Critical international political theory developed by Andrew Linklater claims that the international as a historico-social reality is normatively based on the certain understanding of the relationship between humanity and citizenship which is specifically defined by a particularistic ethical/political ontology. Transforming the modern socio-political community in terms of its normative, historico-social and practical underpinnings by drawing on the standpoint of ethical universalism, it proposes a more universalistic, less unequal and more difference/other sensitive conception of global political theory. This paper argues that even if critical international political theory provides a comprehensive analysis of moral, social and political conditions of the coexistence of multiple socio-political communities in the contemporary world, because of its excessive commitment to modern notions of autonomous subject and sovereignty, it turns out to be conceptually insufficient to grasp the problem of difference, plurality and multiplicity in world politics.
Keywords: Humanity; Socio-political Community; Critical Theory; Andrew Linklater; Universality/Difference; Global Politics; INTERNATIONAL-RELATIONS; SOVEREIGNTY; HABERMAS; QUESTION; ORIGINS; REALISM; SCHOOL; STATE; International Relations